POLICIES AND INSTITUTIONS OF ISLAMIC EDUCATION IN INDONESIA : Kebijakan dan Lembaga pendidikan Islam di Indonesia - M. Alfanny Fahmil Ulum; Afi Rizqiyah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The success of education cannot be separated from the role of policy and institutions. All education implementers need to understand policy and institutional positions. This article aims to review basic information about the policies and institutions of Islamic Education in Indonesia. The research uses a literature method with a qualitative approach. The source of research data is taken from books and scientific articles collected through documentation techniques. The data is then analyzed with stages of data reduction, data presentation, and conclusions. The Islamic Religious Education Policy is a government decision that is used as a guideline in the implementation of Islamic Religious Education and solving various problems in it. Education policy in Indonesia consists of four levels or levels, namely the national policy level, general policy level, special policy level, and technical policy level. While Islamic educational institutions in Indonesia can be categorized into formal, non-formal, and informal institutions. Formal institutions in the form of schools from early childhood to tertiary level are divided into public schools under the Ministry of Education and Culture, and religious schools under the Ministry of Religious Affairs.